2009
DOI: 10.1093/ejo/cjp118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term storage and thermocycling on bond strength of two self-etching primer adhesive systems

Abstract: The effects of 2 years of storage and 6000 thermocycles on the shear bond strength (SBS) of two self-etching adhesive systems were studied. Two self-etching primer (SEP) systems (Transbond Plus and Beauty Ortho Bond) and one etch and rinse system (Transbond XT) were used to bond brackets to 126 human premolars that were then stored in artificial saliva for 24 hours or 2 years and thermocycled in distilled water before SBS testing with a universal testing machine. The adhesive remnant index (ARI) scores were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 18 publications
5
61
2
2
Order By: Relevance
“…That study analyzed thermal cycling associated to different light sources, silane and feldspathic ceramic, while this study used only thermal cycling. However, they disagree with other studies, which found no significant difference in bond strength after thermocycling (5,11). The lack of difference may be explained by the fact that these studies used a smaller number of cycles.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…That study analyzed thermal cycling associated to different light sources, silane and feldspathic ceramic, while this study used only thermal cycling. However, they disagree with other studies, which found no significant difference in bond strength after thermocycling (5,11). The lack of difference may be explained by the fact that these studies used a smaller number of cycles.…”
Section: Discussioncontrasting
confidence: 74%
“…The clinical success and long-term durability of the bond strength between orthodontic brackets and the ceramic surface using composite resin may be influenced by several factors, such as thermal cycling, fatigue, artificial ageing and mechanical properties of composite resin, silane and adhesive bonding (11). The quality and durability of this bond is determined by the specific treatment used to produce chemical and micromechanical retention to the ceramic material (13) and bonding mechanisms between bracket/bonding materials (2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations